The Effect in Cognitive, Affective, and Behavior of Using Electronic Gadget among University Students - Lukman@Zawawi, Mohamad; Normala, Riza; Azlini, Chik (2018)
The problem of using electronic gadgets is increasing as a result of rising modern development and the widespread sophistication of the internet. This main purpose of this study is to identify the effect in cognitive, affective and behavior of electronic gadget among university students. The data was collected through questionnaire and analyzed using descriptive statistics. The descriptive statistic is reported by frequency and percentage to show the effect in cognitive, affective and behavior of electronic gadgets. A total of 352 respondents had completely answered the questionnaire. The result shows behavior effect greatly affects the use of the electronic gadget.